Pragmatic markers in Chinese - Feng, Guangwu (Journal of pragmatics, 2008)
This article presents a principled and systematic description of pragmatic markers in Chinese. Pragmatic markers (and a range of interconnected categories including discourse particles and the like) in English and some other languages have been the subject of intensive investigation. However, markers of this sort in Chinese have been largely ignored. This article first defines pragmatic markers as syntactically dispensable, truth-conditionally irrelevant expressions operating on the propositional content of the sentence to which they are attached. Given that pragmatic markers enjoy these general properties some expressions which are usually included in the domain are counted out. The article then makes a distinction between conceptual and non-conceptual pragmatic markers. Finally, the article presents a typology of pragmatic markers in Chinese, describing in a detailed way the semantic, morphological and syntactic properties of each subtype of both conceptual and non-conceptual pragmatic markers in Chinese.